(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the influence of tourist attractions and facilities on the decision to visit Guci Tegal Hot Springs, with interest in visiting as an intervening variable. Data were obtained from visitor questionnaires and analyzed using SEM-PLS through SmartPLS. The results show that attractions and facilities have a significant effect on visiting interest, which in turn affects visiting decisions. Visiting interest is proven to mediate the relationship between the two variables on visiting decisions